FUNCTIONAL STATUS IN PATIENTS WITH CHRONIC KIDNEY DISEASE BEING TREATED WITH HEMODIALYSIS IN PKU MUHAMMADIYAH HOSPITAL, YOGYAKARTA, INDONESIA - Adiyati Mardiyah; Anggorowati Anggorowati; Andrew Johan (Belitung Raya Foundation, Indonesia, 2017)
Background: Hemodialysis process is useful for patients with end-stage renal disease. However, this is a situation of abject dependence on a machine, a procedure and a group of qualified medical professionals for the rest of their lives that may influence their functional status. Objective: This study aims to describe the functional status of patients with chronic kidney disease undergoing hemodialysis. Method: This was a descriptive study with cross-sectional design, which conducted in the PKU Muhammadiyah Hospital Yogyakarta Indonesia on March 2017. There were 78 patients selected using purposive sampling. Functional status was measured using SF-36 questionnaire. Descriptive statistic was performed for data analysis Result: The total average of functional status level was 42.92, with Physical Component Scale (PCS) of 42.31 and Mental Component Scale (MCS) of 45.78. Conclusion: There were functional deficiencies in both physical and mental status in patients with chronic kidney disease undergoing hemodialysis. Thus, it is suggested that pharmacological management of these patients need stringent monitoring on part of the psychiatrist to deal with mental health problems, and the interdisciplinary team need to do great efforts to improve functional status and quality of life of patients with chronic kidney disease.